Ogólnopolska konferencja naukowa „Szybkość w kulturze”, Warszawa 20–21 maja 2015 r. - Smaga, Agnieszka (Załącznik Kulturoznawczy, 2023)
Ogólnopolska konferencja naukowa „Szybkość w kulturze”, Warszawa 20–21 maja 2015 r.